Rehabilitation With Bridging Exercise In Stroke Patients: Systematic Review - Fauziah Rochmah, Ardianti; Septianingrum, Yurike; Lono Wijayanti; Umdatus Soleha (Journal of Applied Nursing and Health, 2024)
Background: Stroke is a neurological disease that can result in weakness in part or all of the body, emphasizing the importance of early mobilization in post-stroke recovery. One of the fundamental physical exercises recommended is the bridging exercise. This article evaluates the impact of bridging exercises on stroke patients through a systematic review approach, focusing on their potential to improve rehabilitation outcomes. Methods: The methodology involved a systematic review of studies from 2020 to 2024, using journal databases such as Google Scholar, Science Direct, and PubMed. Keywords like "Bridging exercise," "Stroke," "Stroke patients," "Rehabilitation," "Muscle strength," and "Body balance" guided the search. Articles included in the review were in English and selected based on PRISMA guidelines, resulting in seven eligible studies for analysis. Results: The results of this review highlight that bridging exercises significantly improve muscle strength and body balance among stroke patients. The exercises demonstrated a positive influence on patients' rehabilitation progress, contributing to better physical and functional health outcomes. Conclusion: In conclusion, bridging exercises serve as an effective intervention in stroke rehabilitation, promoting early mobilization and improving post-stroke recovery. Encouraging stroke patients to incorporate these exercises into their rehabilitation routines could enhance overall health and functional capabilities.